MORPHOFUNCTION CHANGES IN SHEEP PARAMPHISTOMATOSIS (Conferencea, 2023)
In this article, morphofunctional changes in parenchymatous and digestive organs in sheep paramphistomatosis are presented on the basis of histological examinations.